Monodisperse Pt atoms anchored on N-doped graphene as efficient catalysts for CO oxidation: a first-principles investigation. Issue 3 (16th December 2014) - Liu, Xin; Sui, Yanhui; Duan, Ting; Meng, Changgong; Han, Yu
Abstract : The Pt–N interaction tunes the energy of Pt states and makes the Pt atoms stabilized on N-doped graphene excellent for CO oxidation. Abstract : We performed first-principles based calculations to investigate the electronic structure and the potential catalytic performance of Pt atoms monodispersed on N-doped graphene in CO oxidation. We showed that N-doping can introduce localized defect states in the vicinity of the Fermi level of graphene which will effectively stabilize the deposited Pt atoms. The binding energy of a single Pt atom onto a stable cluster of 3 pyridinic N (PtN3) is up to −4.47 eV, making the diffusion and aggregation of anchored Pt atoms difficult. Both the reaction thermodynamics and kinetics suggest that CO oxidation over PtN3 would proceed through the Langmuir–Hinshelwood mechanism. The reaction barriers for the formation and dissociation of the peroxide-like intermediate are determined to be as low as 0.01 and 0.08 eV, respectively, while that for the regeneration is only 0.15 eV, proving the potential high catalytic performance of PtN3 in CO oxidation, especially at low temperatures. The Pt-d states that are up-shifted by the Pt–N interaction account for the enhanced activation of O2 and the efficient formation and dissociation of the peroxide-like intermediate.